A Numerical Study on Impact of Taiwan Island Surface Heat Flux on Super Typhoon Haitang (2005) - Hongxiong Xu (Advances in Meteorology)
Three to four tropical cyclones (TCs) by average usually impact Taiwan every year. This study, using the Developmental Tested Center (DTC) version of the Hurricane WRF (HWRF) model, examines the effects of Taiwan’s island surface heat fluxes on typhoon structure, intensity, track, and its rainfall over the island. The numerical simulation successfully reproduced the structure and intensity of super Typhoon Haitang. The model, especially, reproduced the looped path and landfall at nearly the right position. Sensitive experiments indicated that Taiwan’s surface heat fluxes have significant influence on the super Typhoon Haitang. Compared to sensible heat (SH) fluxes, latent heat (LH) is the dominant factor affecting the intensity and rainfall, but they showed opposite effects on intensity and rainfall. LH (SH) flux of Taiwan Island intensified (weakened) Typhoon Haitang’s intensity and structure by transferring more energy from (to) surface. However, only LH played a major role in the looped path before the landfall of the Typhoon Haitang.